Molecular and phenotypic characterization of 'Agrobacterium' species from vineyards allows identification of typical 'Agrobacterium vitis' and atypical biovar 1 strains - Genov, N.; Llop, Pablo; López, María M.; Bobev, S. G.; Álvarez, Belén (2017)
Aim: To molecularly and phenotypically characterize a selection of Agrobacterium-like isolates from grapevine canes, crowns, soil and tumours in plants grown under cold conditions. Methods and Results: Most of the strains were biovar 3 (Agrobacterium vitis), and the remaining were atypical biovar 1 (Agrobacterium tumefaciens). All of them were tumourigenic on grapevine plants but differences in other hosts were observed. Chromosomal and plasmid-borne traits were analysed by gene amplification with four primer sets. Detection of the pectin enzyme hydrolase gene clearly distinguished A.vitis from the atypical A.tumefaciens. Regarding the virulence sensor gene, limited host range tumour-inducing plasmids were found in the atypical isolates. About opine utilization, most A.vitis and some A.tumefaciens contained octopine/cucumopine plasmids, but the nopaline-type was only detected in one A.tumefaciens. Conclusions: The A.vitis strains were molecularly and phenotypically more homogeneous than those of A.tumefaciens, the latter displaying some typical A.vitis characteristics, suggesting an adaptation to life in grapevine. Significance and Impact of the Study: The findings of this work will help to improve detection procedures of the pathogen, and demonstrate the pathogen diversity in cold vineyards, laying the groundwork for epidemiological studies and development of control strategies of the crown and cane gall disease.